Plotinus and the moving image - Botz-Bornstein, Thorsten. (Value Inquiry Book Series, 2018)
Plotinus and the Moving Image offers the first philosophical discussion on Plotinus' philosophy and film. It discusses Plotinian concepts like \'the One\' in a cinematic context and relates Plotinus' theory of time as a transitory intelligible movement of the soul to Bergson's and Deleuze's time-image. Film is a unique medium for a rapprochement of our modern consciousness with the thought of Plotinus. The Neoplatonic vestige is particularly worth exploring in the context of the newly emerging "Cinema of Contemplation." Plotinus' search for the \'intelligible\' that can be grasped neither by sense perception nor by merely logical abstractions leads to a fluent way of seeing. Parallels that had so far never been discussed are made plausible. This book is a milestone in the philosophy of film. Contributors are: Cameron Barrows, Thorsten Botz-Bornstein, Michelle Phillips Buchberger, Steve Choe, Stephen Clark, Vincenzo Lomuscio, Tony Partridge, Daniel Regnier, Giannis Stamatellos, Enrico Terrone, Sebastian F. Moro Tornese and Panayiota Vassilopoulou.